Do We Care? India’s Health System - Aditya Singh, (National Geographical Journal of India, 2021)
The book intends to question our lax attitude towards the problems of our country. It complains that we make laws and policies, but rarely care about implementing them in their true letter and spirit. The book offers great insights into numerous challenges India’s health system has faced in the past, how it has dealt with them, and how successful it has been in tackling them.